Long-term debt and financial performance - Desy Astrid Anindya; Harry Suharman; Indawati Lestari; Muhammad Habibie (Journal of Innovation in Business and Economics, 2025)
This study aims to analyze the influence of capital structure on the financial and market performance of construction companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period. Capital structure is measured by the proportion of long-term debt to total capital. Financial performance is assessed using Return on Equity (ROE), while market performance is proxied by stock price. The analysis employs panel data regression with a fixed effects approach, controlling for firm size, liquidity, interest coverage ratio, and sales growth. The results show that long-term debt has a negative and significant effect on ROE, but no significant effect on the stock price. Conversely, the current ratio and sales growth have a positive and significant effect on ROE, while the current ratio and firm size significantly increase stock prices. These findings suggest that the inappropriate use of long-term debt may reduce profitability, and that investors place greater emphasis on liquidity and firm size when assessing market value. This study contributes to the literature on capital structure in the construction sector, which is characterized by capital-intensive and high-risk operations. Practically, the findings can inform company management in formulating more efficient and sustainable financing strategies and help investors interpret financial signals relevant to firm value.